2000
DOI: 10.1149/1.1393198
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Concentration Limitation in Czochralski Silicon Crystals

Abstract: The maximum phosphorus concentration that can be incorporated in a silicon crystal using the Czochralski crystal growth method was investigated. The value was found to be related to the hot-zone configuration and is about 1.11 ϫ 10 20 atom/cm 3 for 100 mm (111) crystals grown from a short tank grower with an 18 kg charge size. This doping concentration corresponds to a resistivity value of 0.00071 ⍀-cm. When the tang-end of a growing crystal reached this doping concentration, dislocations were generated at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…This means Constitutional Supercooling in Czochralski Growth ... 225 that a breakdown of the interface caused by constitutional supercooling will preferentially begin in the core of the crystal rather than at its periphery. This prediction is conrmed by several experimental results [3,715].…”
Section: Discussionsupporting
confidence: 64%
“…This means Constitutional Supercooling in Czochralski Growth ... 225 that a breakdown of the interface caused by constitutional supercooling will preferentially begin in the core of the crystal rather than at its periphery. This prediction is conrmed by several experimental results [3,715].…”
Section: Discussionsupporting
confidence: 64%
“…Phosphorus and arsenic are in an intermediate situation, having a segregation coefficient of 0.35 and 0.3, respectively. Very few publications are available on the minimum obtainable resistivity for these dopants [5,6] especially in the case of <100> oriented, large diameter crystals. For these cases the present authors have found a limit at about 1 and 2 mΩ·cm for 200 mm phosphorus and arsenic crystals, respectively.…”
Section: Constitutional Supercoolingmentioning
confidence: 99%
“…The result is very heavily doped twodimensional silicon, with typically 1/180 P atoms/Si atom (taking into account the actual layer thickness, as referred to later). For comparison, the solubility limit of P in bulk CZ-grown Si is 1/450-1/250 impurities/Si atoms [3,4], and the highest densities for activated subsurface ion implanted layers correspond to 1/80 P/Si [5]. Furthermore, for the two-dimensional electron gases produced in Si metal-oxidesemiconductor field-effect transistors (MOSFETs), the carrier densities are typically 10 12 −10 13 cm −2 , corresponding to 1/5000-1/50000 electrons/Si, where we assume an inversion layer thickness of 10 nm [6].…”
Section: Introductionmentioning
confidence: 99%